Global Supply Chains and Corporate Social Responsibility: Navigating Ethical and Sustainable Business Practices - Anouar Hana; Kasbaoui Tarik (African Scientific Journal, 2025)
Abstract In today’s globalized world, global supply chains are essential for the efficient functioning of world trade. However, these far-reaching networks frequently raise significant issues related to ethics, sustainability, and social responsibility. Corporate social responsibility (CSR) is increasingly being considered as a strategic instrument to address these challenges and ensure that companies make a positive contribution to society and the environment. This article examines the integration of CSR into global supply chains, providing a detailed study of ethical issues such as labor rights, environmental impacts, and transparency. Through an in-depth literature review and a study of 15 corporate cases, this article explores different models of corporate social responsibility (CSR), the evolution of stakeholder expectations, and the contribution of companies to ethical conduct in their supply chains. Drawing on empirical observations and concrete examples of good practices, it highlights varied approaches to CSR implementation. The analysis shows that the progressive integration of CSR principles into global supply chains strengthens resilience, improves transparency, and contributes to sustainable value creation for all stakeholders. Keywords Global supply chains, corporate social responsibility, business ethics, sustainability, labor rights, environmental impacts, supply chain transparency, ethical sourcing